Comparative Analysis of Circular and Spin Fin Pile for Axial Loading - et.al, Poonam Gawande, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Conventional circular piles are more commonly used for onshore as well as offshore structures due to their ease of installation. However, in some crictical cases to develop significant vertical capacity during driving the use these circular piles are not reliable. Spin fin pile foundation is an innovative modification over a conventional circular pile foundation. Spin fin piles are traditional pipe piles fitted with steel plates; fins are attached at a slight angle over the upper or bottom portion of circular piles. This paper presents a numerical solution for axially loaded circular pile and triangular shape spin fin pile group in linear-elastic soil proﬁles. In this study, a MIDAS GTS-NX software is used to developed model. The behaviour of circular pile and triangular shape spin fin pile with loose sand and medium dense sand for different slenderness ratio are examined. The load dispensation within the circular and fin pile and the settlement of pile are shown. Analysis shows that, the vertical resistance increases in triangular shape spin fin pile as compare to circular pile.